Survival and outcomes for stroke survivors living in care homes: a prospective cohort study. (6th July 2021) - Clery, Amanda; Martin, Finbarr C; Redmond, Patrick; Marshall, Iain; McKevitt, Christopher; Sackley, Catherine; Manthorpe, Jill; Wolfe, Charles; Wang, Yanzhong
Abstract: Background: Stroke survivors living in care homes require high levels of support with everyday living. The aims of this study were to describe the survival, health status and care received by stroke survivors living in care homes at 1-year post-stroke, compared with those in their own homes. Methods: A total of 3, 548 stroke survivors with a first ever stroke between 1998 and 2017 in the South London Stroke Register were identified for survival analysis. A total of 2, 272 were included in the 1-year follow-up analysis. Cox regression and Kaplan–Meier plots were used to describe survival, stratified into four 5-year cohorts. Health status, medications and rehabilitation received at 1-year post-stroke were compared using descriptive statistics. Results: Over the 20-year period, survival improved for stroke survivors discharged to their own home ( P < 0.001) but not for those discharged to care homes ( P = 0.75). Care home residents were highly disabled (median Barthel index: 6/20, interquartile range: 2–10). Rates of secondary stroke prevention medications at 1-year follow-up increased over time for care home residents, including antiplatelets from 12.3 to 38.1%, although still lower than for those in their own homes (56.3%). Speech and language problems were common in the care home population (40.0%), but only 16% had received speech and language therapy. Conclusions: Rates of secondary stroke prevention prescribing increased over 20 years but remained lower in care home residents. The lower levels of rehabilitation received by stroke survivors in care homes, despite their higher levels of disability, suggest a gap in care and urgent need for restorative and/or preventative rehabilitation.